Julius Ohm-Januschowsky in njegovo kritiško delo v Ljubljani - Lah, Špela (Muzikološki zbornik, 2007)
German journalist of Czech origin, Julius Ohm- Januschowsky, was one of more important personalities in music journalism of the last quarter of 19th century in Ljubljana. His main work was to report and evaluate music-theatrical performances. His contribution to the reestablishment of the quality of Ljubljana's musical life was, therefore, essential. The present article tries to reveal the main characteristics of his critical work. The main sources were the daily newspaper Laibacher Zeitung and important critiques by Januschowsky written between 1892 (when he took over the task of critiquing music-theatrical performances) and 1915 (when is assumed to have left Ljubljana).
Keywords: glasba; kritika; music; Ohm-Januschowsky, Julius; operne predstave